Allocation of Human Capital and Innovation at the Frontier: Firm-Level Evidence on Germany and the Netherlands - Eric Jan Bartelsman; Sabien Dobbelaere; Bettina Peters (Institute for the Study of Labor (IZA), 2013)
This paper examines how productivity effects of human capital and innovation vary at different points of the conditional productivity distribution. Our analysis draws upon two large unbalanced panels of 6,634 enterprises in Germany and 14,586 enterprises in the Netherlands over the period 2000-2008, considering 5 manufacturing and services industries that differ in the level of technological intensity. Industries in the Netherlands are characterized by a larger average proportion of high-skilled employees and industries in Germany by a more unequal distribution of human capital intensity. Except for low-technology manufacturing, average innovation performance is higher in all industries in Germany and the innovation performance distributions are more dispersed in the Netherlands. In both countries, we observe non-linearities in the productivity effects of investing in product innovation in the majority of industries. Frontier firms enjoy the highest returns to product innovation whereas the most negative returns to process innovation are observed in the best-performing enterprises of most industries. In both countries, we find that the returns to human capital increase with proximity to the technological frontier in industries with a low level of technological intensity. Strikingly, a negative complementarity effect between human capital and proximity to the technological frontier is observed in knowledge-intensive services, which is most pronounced for the Netherlands. Suggestive evidence for the latter points to a winner-takes-all interpretation of this finding.
Keywords: C10; I20; O14; O30; 330; human capital; innovation; productivity; quantile regression